Audit of intrathecal drug delivery for patients with difficult-to-control cancer pain shows a sustained reduction in pain severity scores over a 6-month period. (June 2015) - Mitchell, Alison; McGhie, Jonathan; Owen, Margaret; McGinn, Gordon
Background: Intrathecal drug delivery is known to be effective in alleviating cancer pain in patients for whom the conventional World Health Organization approach has proved insufficient. A multidisciplinary interventional cancer pain service was established in the West of Scotland in 2008 with the aim of providing a safe and effective intrathecal drug delivery service for patients with difficult-to-control cancer pain. Aim: The aim of the intrathecal drug delivery service is to improve pain scores as evaluated by pain scores before and after insertion of an intrathecal drug delivery device. Design: Pain is monitored before and after intrathecal drug delivery implantation using the Brief Pain Inventory. Following implantation, pumps are refilled fortnightly and repeat Brief Pain Inventory assessments are undertaken. This prospective case series analyses change in Brief Pain Inventory domains for patients who had an intrathecal drug delivery implanted using a paired sample t -test. Results: Data are presented from 2008–2013 for 22 patients receiving an intrathecal drug delivery system who experienced an immediate improvement in their pain that was both clinically and statistically significant. One week after insertion, the average pain score on the Brief Pain Inventory fell from 6.8 (pre–intrathecal drug delivery) to 3.0 (post–intrathecal drug delivery). Improvement in pain scores was sustained over a 6-month period. Conclusion: Evaluation of results of this case series shows that with the appropriate use of intrathecal drug delivery systems, patients with difficult-to-control cancer pain can benefit from effective pain relief for many months.